2019
DOI: 10.1108/jstpm-03-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management practices and innovation performance

Abstract: Purpose This paper aims to concentrate on the conscious and systematic managerial activities associated with handling knowledge in an organization [i.e. knowledge management (KM) practices] for the purpose of improving innovation performance through proactive management of knowledge assets. This study explores the impact of KM practices on innovation performance in the research and training center of government apparatus. Design/methodology/approach This research provides empirical evidence on how various KM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 28 publications
(62 reference statements)
1
13
0
1
Order By: Relevance
“…Nevertheless, if companies are to have better performance, it is suggested that they rely on a incentive system for knowledge activities (Omoush, 2018). A government sector study found that innovation performance decreases when the improvement of knowledge is rewarded (Susanty et al, 2019); perhaps this divergence is the result from not calculating a break-even point, since investments in knowledge management tend to have a maximum effect, from which innovation slows down (Teixeira et al, 2018).…”
Section: Empirical Studies Related To Study Variablesmentioning
confidence: 99%
“…Nevertheless, if companies are to have better performance, it is suggested that they rely on a incentive system for knowledge activities (Omoush, 2018). A government sector study found that innovation performance decreases when the improvement of knowledge is rewarded (Susanty et al, 2019); perhaps this divergence is the result from not calculating a break-even point, since investments in knowledge management tend to have a maximum effect, from which innovation slows down (Teixeira et al, 2018).…”
Section: Empirical Studies Related To Study Variablesmentioning
confidence: 99%
“…Since RC dimensions are essentially about integrating resources, sharing, and acquiring knowledge to achieve firm financial performance, they are dependent on integrability of actors into business ecosystem. We identify two highlighted conditions: partner integration mode as a source of external knowledge (Adams & Graham, 2017) and the management of this knowledge (Susanty, Yuningsih, & Anggadwita, 2019). In what follows, we present these conditions influencing RC dimensions relationships as potential factors for firm financial performance.…”
Section: Potential Moderators Of the Rc Dimensionsmentioning
confidence: 99%
“…It's necessary for managers to handle with finesse and under wisdom the challenge of knowledge management due to the fact that it is closer of human mind (Lundvall & Nielsen, 2007). Therefore, as a structured and systematic effort, knowledge management is crucial in decision-making process towards organizational performance (Susanty et al, 2019) and this process can leverage relational capabilities on the search of these performance achievements.…”
Section: Potential Moderators Of the Rc Dimensionsmentioning
confidence: 99%
“…Scholars defined knowledge Management as a concept that depends on collecting, auditing and sharing information within the organization's stakeholders (employees, customers and partners). While Susanty, Yuningsih, & Anggadwita (2019) claim that knowledge management is a learning process that involves exploration, exploitation and share of knowledge supported by optimum technology and cultural environment. Gunjal (2019), emphases in his definition the importance of sharing information and data within the organization to enhance the capability of running a business efficiently and effectively.…”
Section: Knowledge Management and Employee Performancementioning
confidence: 99%